Low-coherence and broadband confocal refractometry: reducing the measurement time - Francis, Daniel; Hallam, Jonathan M.; Tatam, Ralph P. (IOP Publishing, 2023)
This paper describes the steps taken to improve the measurement speed of a combined low-coherence and confocal refractive index measurement system. The instrument measures the refractive index and thickness of transparent plates using a fibre-based low-coherence interferometer with a line-scan spectrometer. The spectrometer allows on-line dispersion measurement which is necessary to derive the sample thickness t as well as both the phase and group refractive indices np, ng. The measurements were performed on a sample with six surfaces consisting of three glass windows mounted in a lens tube. Experimental results show that a measurement time of 4.4 s for the multi-layered object, which has a total thickness of approximately 10.5 mm, can be achieved whilst maintaining an accuracy of better than 0.1% for np, ng, and t. This represents an approximately hundredfold improvement over previously published measurements.
Keywords: confocal; refractometry; refractive index measurement; low-coherence interferometry; dispersion; peak detection